Religious tolerance value analysis perspective teachers of Islam, Christian and Catholic religious education in SMK Demak - Ukhiya Rizqiany (IAIN Salatiga, 2017)
These days there are often sara issues about religious tolerance, so it makes the attention both among professionals, general public, even the students. Therefore, educators need to pay attention to the problem. In this case the role of Teacher of Religious Education is important in forming the students' point of view about religious tolerance. This paper aims to analyze the perspective of Islamic Education Teachers, Christian and Catholic especially in SMK Negeri 1 Karangawen and SMK Bhakti Nusantara Mranggen Demak. The two Vocational High Schools were chosen because Karangawen sub-district is the most church-dominated environment in Demak District, and both of them provide facilities for non-Muslims citizen to send their children to SMK that provides teachers of Islamic, Christian and Catholic Religious Education. This research is field research (field research) with qualitative approach, phenomenology method. Technique of collecting data using interview, to know perspective / point of view of religion teacher for planting tolerance value of the students. In this study found that from the three perspectives of teachers of Religious Education has its own limits in religious tolerance that is conveyed to students. Even indicated there is a perspective from Religious Education Teachers who are worried about entering the domain of compromise in religious tolerance.